THE ROLE OF TEACHERS IN BUILDING STUDENT CHARACTER AT SINDANGSARI 02 STATE ELEMENTARY SCHOOL - Ananda Rivaldo Sari (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2021)
Education is a conscious, orderly and systematic effort in providing guidance or assistance to other people (children) who are progressing towards adulthood, the role of the teacher is not only as a teacher, academic educator but also as character, moral and cultural educator for students. The teacher must be a role model, a model as well as a mentor of students in realizing characterful behavior which includes thought, heart and feeling. Cultivating and developing character education in schools is a shared responsibility. Character education can be integrated in learning in every subject. Every subject related to the norms or values ​​in each subject needs to be developed, made explicit, related to the context of everyday life. The learning of these character values ​​does not stop at the cognitive level, but touches at the level of internalization and real practice in the daily lives of students in society. Character education is now absolutely necessary not only in schools, but at home and in the social environment. Even now character education is no longer just for early childhood to adolescents, but also for adults. Character education is expected to be able to answer the challenges and progress of an increasingly advanced era. The method used in this research is a qualitative approach to examine natural behavior and events. Descriptive type is used to describe real events in a relationship of facts by using detailed words to accurately reflect data from complex human behavior.